Iris Murdoch and the Art of Imagining. By Marije Altorf - Jasper, David (Literature and theology, 2009)
Marije Altorf's book on Iris Murdoch is elegant in its brevity, cultivating a style that celebrates the art of imagining and it is as suggestive and ultimately elusive as her subject, whose work as a philosopher and a novelist Altorf illuminates through intelligent conversation, witty analysis and careful interpretation. Iris Murdoch was one of an early generation of Oxford women philosophers, together with Elizabeth Anscombe, Mary Midgley, Mary Warnock and others, who entered as professionals, the male dominated university library which, only 10 years before, Virginia Woolf had stood outside and cursed.